The Effect of Different Light Curing Units and Composite Thicknesses on the Shear Bond Strengthof Composite to Dentin - Ali asgar Alavi; Fatemeh Koohpeima; Mehran Motamedi; Somayeh Heidari (Islamic Dental Association of Iran, 2013)
Background and Aim : Development of new composite resins is one of the most important technological advances in the field of cosmetic dentistry. The aim of this study was to investigate the effectiveness of different light curing units and composite thicknesses on the shear bond strength composite to dentin .   Materials and Methods : In this experimental in-vitro study, the test groups were composed of 80 dentinal samples, prepared on occlusal surfaces of 80 maxillary premolar teeth and routinely divided into 8 groups of 10. Two cylindrical molds (2×2 and 2×5 mm) were filled in bulk using P60 and Ceram X composites and light cured with LED and QTH light curing units .After curing and 3 months aging in 370c water, shear bond strength of all samples were obtained using a universal testing machine with 1mm/min crosshead speed. One- and three-way ANOVA were used for statistical analysis using SPSS software .   Results : The highest mean of shear bond strength (31.75 MPa) was in group (P60, QTH, 2) and the lowest (15.34 MPa) was recorded in (Ceram X, LED, 5). Type and thickness of composites had significant effects on the value of shear bond strength and no significant differences were obtained between two light curing units .   Conclusion : The shear bond strengths of P60 and CeramX composites tested were much lower when cured in a 5-mm than in a 2-mm increment. The two types of light curing units tested did not show any significant differences in the amount of shear bond strengths .